Appropriate Commentary Register in a Match of Volleyball Men’s Nations League 2019 - Raisa, Nabilah; Farkhan, Muhammad (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
This research examines the register by the commentator’s utterance in the video “France vs. Japan - Full Match | Men’s Volleyball Nations League 2019. This research aims to discover the register and its meanings in volleyball and explore the appearance of register by paying attention to field, mode, and tenor in utterances made by the commentators in Volleyball Men’s Nations League 2019. The researcher used qualitative methods with descriptive and analysis techniques by using Halliday’s register theory. This research shows that in fields, language is used to explain a situation’s context and create social relations. The mode shows how the speaker conveys his message, which involves spoken or written communication. In tenor, the commentator considers the audience equal so that it shows minimal social distance due to the use of informal forms of language, such as the colloquial, the tone, and the choice of words. In conclusion, using registers helps meet communication needs between experts in their fields because they represent languages whose functions are for specific purposes.